Epistemological Beliefs of Mathematics Teachers about Mathematics, its Teaching and its Relationship to Teaching Practice (2017)
This research paper presents the result of a research process whose objective was to analyze and describe the epistemological beliefs that athematics teachers have about mathematics, its teaching and their relation with their actual teaching practice. The case study methodology was used involving three teachers, each one of them with over ten years of experience, who conducted a short course about a historical tour of quadratic equations, which was aimed to challenge the epistemological beliefs of the participants and to promote reflections on the matter. In order to collect the information closed questionnaires were applied, semi-structured interviews were conductedand teachers presented a proposal for teaching quadratic equations incorporating the aspects studied in the course. The results evidenced that teachers have endeavored to build a coherent epistemology between mathematics and its teaching and learning, but difficulties do persist.